MRI-PDFF Assessment of Intrahepatic Fat Changes Post-Bariatric Surgery: A Systematic Literature Review - Danut Dejeu; Paula Dejeu; Anita Muresan; Paula Bradea; Viorel Dejeu (Medicina)
Background and Objectives: Non-alcoholic fatty liver disease (NAFLD) is prevalent among obese individuals and can progress to non-alcoholic steatohepatitis (NASH). Bariatric surgery is known to induce significant weight loss and may improve NAFLD. This systematic review uniquely synthesizes current evidence on the effects of bariatric surgery on intrahepatic fat content, measured by magnetic resonance imaging proton density fat fraction (MRI-PDFF), and assesses study quality using the Newcastle–Ottawa Scale (NOS). Materials and Methods: The literature search was conducted across the PubMed, Scopus, and Web of Science databases up to October 2024, identifying 12 prospective cohort studies involving 613 patients who underwent bariatric surgery. Inclusion criteria included adult patients with NAFLD undergoing bariatric surgery, assessment of liver fat changes using MRI-PDFF before and after surgery, and studies reporting quantitative data on liver fat fraction and relevant clinical parameters. Data extraction focused on patient demographics, surgical procedures, specific weight loss outcomes (delta BMI), changes in intrahepatic fat content (delta MRI-PDFF), and quality assessment scores based on the NOS. Results: Significant reductions in intrahepatic fat content were observed across all studies, with delta MRI-PDFF reductions ranging from 6.9% to 14%. Weight loss outcomes varied, with excess weight loss percentages up to 81.3% and BMI reductions up to 12 kg/m². The quality assessment scores ranged from six to nine out of nine, indicating generally high-quality studies. Correlations were noted between the degree of weight loss and reduction in liver fat content. Several studies reported high rates of resolution of steatosis and NASH post-operatively. Conclusions: Bariatric surgery leads to significant reductions in intrahepatic fat content and improvements in NAFLD among obese patients. The degree of weight loss correlates with the reduction in liver fat. These findings underscore the clinical utility of bariatric surgery as a strategic intervention for managing NAFLD in obese individuals, potentially influencing clinical practice guidelines by integrating bariatric surgery as a viable treatment option for NAFLD-related hepatic conditions.